The comparison of acute and gradual weight loss methods in well-trained wrestlers - Rashidlamir, A.; Goodarzi, M.; Ravasi, A. (World Journal of Sport Sciences, 2009)
The aim of this research is to compare two weight loss methods (acute and gradual) in well-trained wrestlers. 30 well-trained wrestlers participated in this research voluntarily and then were randomly divided into two groups: Group A (n=15) and group B (n=15). Their percentage of body fat (measured with caliper), strength and endurance of upper and lower extremities were measured before and after the weight lose program. All subjects were required to lose 4% of their body weight. Group A (recommended) lost their weight according to a special diet program during 12 days and group B according to the traditional method: severe diet and sauna. Results showed that endurance of upper and lower extremities, strength of upper extremity decreased significantly (P<0.01) and body fat percentage and strength of lower extremity did not change significantly in group B. But, despite of a significant decrease in body fat percentage, none of the mentioned variables changed significantly in group A. We recommend wrestlers to use this gradual weight loss method in order to maintain the physiologic parameters of their body, to lose weight without harmful side effects and to have better performance.